2015
DOI: 10.1103/physrevb.92.245439
|View full text |Cite
|
Sign up to set email alerts
|

An artificial Rb atom in a semiconductor with lifetime-limited linewidth

Abstract: We report results important for the creation of a best-of-both-worlds quantum hybrid system consisting of a solid-state source of single photons and an atomic ensemble as quantum memory. We generate single photons from a GaAs quantum dot (QD) frequency matched to the Rb D2 transitions and then use the Rb transitions to analyze spectrally the quantum dot photons. We demonstrate lifetime-limited QD linewidths (1.42 GHz) with both resonant and nonresonant excitation. The QD resonance fluorescence in the low power… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 44 publications
4
88
1
Order By: Relevance
“…But when translated to the visible spectrum (roughly 380-780 nm), such a wavelength difference could be discriminated with the bare eye. In the future, the methods that Clemmen et al have demonstrated could be used to interface quantum systems operating at different frequencies, such as solid-state and atomic quantum memories [5][6][7][8]. One could envision two physically different quantum memories, each absorbing one part of the single photon in a frequency superposition.…”
mentioning
confidence: 99%
“…But when translated to the visible spectrum (roughly 380-780 nm), such a wavelength difference could be discriminated with the bare eye. In the future, the methods that Clemmen et al have demonstrated could be used to interface quantum systems operating at different frequencies, such as solid-state and atomic quantum memories [5][6][7][8]. One could envision two physically different quantum memories, each absorbing one part of the single photon in a frequency superposition.…”
mentioning
confidence: 99%
“…There, control over the spectral and temporal properties of the exchanged photons is desirable for efficient information transfer [5,6], but can be hard or impractical to implement. A common problem in hybrid quantum networks is a mismatch between the characteristic time scale (or bandwidth) of photons emitted by one node with the optical transition of the receiving node [7][8][9][10][11]. Understanding the role of the photon bandwidth in light-matter interaction is therefore important for the further development of hybrid networks.…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter, we present such a memory based on warm rubidium vapor. The developed memory can readily be combined with a well-engineered GaAs/AlGaAs QD single photon source [8,17,18] and may then serve as a network node, bringing the vision of functional quantum networks closer to reality.Many different physical platforms for quantum memories are currently under investigation, ranging from phonons in solids to atomic Bose-Einstein-condensates [5,19] [17,18,27], a remaining challenge for building a QD compatible atomic memory is that the required acceptance bandwith of δf ¼ 0.5 − 1.0 GHz [28,29] is rather large compared to the intrinsic linewidth of the alkali D lines, which is on the order of δ Rb ¼ 5 MHz [30].One approach to tackle the bandwidth mismatch is to use a far-detuned Raman scheme and dense alkaline vapors [25]. However, this scheme is intrinsically prone to four-wavemixing (FWM) noise [31], impeding experiments in the…”
mentioning
confidence: 99%
“…In this Letter, we present such a memory based on warm rubidium vapor. The developed memory can readily be combined with a well-engineered GaAs/AlGaAs QD single photon source [8,17,18] and may then serve as a network node, bringing the vision of functional quantum networks closer to reality.…”
mentioning
confidence: 99%
See 1 more Smart Citation